2013
DOI: 10.1371/journal.pone.0064372
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects C6 Astrocyte Cell Line against Hydrogen Peroxide-Induced Oxidative Stress through Heme Oxygenase 1

Abstract: Resveratrol, a polyphenol presents in grapes and wine, displays antioxidant and anti-inflammatory properties and cytoprotective effect in brain pathologies associated to oxidative stress and neurodegeneration. In previous work, we demonstrated that resveratrol exerts neuroglial modulation, improving glial functions, mainly related to glutamate metabolism. Astrocytes are a major class of glial cells and regulate neurotransmitter systems, synaptic processing, energy metabolism and defense against oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 94 publications
1
77
0
1
Order By: Relevance
“…Labeled astrocytes in these groups were large and presented with neurodegeneration-related glia activation (astrogliosis). It has been shown that astrogliosis involves an increase in size and count of astrocytes and other glia cells in affected brain regions or inflamed tissue sites and can serve as an indicator of oxidative stress [35] , which can be induced by superoxide anion [36] . GFAP immunohistochemistry in this study further showed that rats treated with NaN 3 have reactive astroglia peculiarly concentrated within the granule cell layer.…”
Section: Gbc Prevents Astrogliosis and Nf Pathology In Cerebellar Cortexmentioning
confidence: 99%
“…Labeled astrocytes in these groups were large and presented with neurodegeneration-related glia activation (astrogliosis). It has been shown that astrogliosis involves an increase in size and count of astrocytes and other glia cells in affected brain regions or inflamed tissue sites and can serve as an indicator of oxidative stress [35] , which can be induced by superoxide anion [36] . GFAP immunohistochemistry in this study further showed that rats treated with NaN 3 have reactive astroglia peculiarly concentrated within the granule cell layer.…”
Section: Gbc Prevents Astrogliosis and Nf Pathology In Cerebellar Cortexmentioning
confidence: 99%
“…Our group has previously demonstrated the interplay between guanosine and the enzyme heme oxygenase 1 (HO-1) [12,14], which is the major enzyme responsible for the conversion of heme into CO and the antioxidant products biliverdin and bilirubin [15,16]. It has been reported that HO-1 may be a therapeutic target in the aging process and/or neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HO-1 may be a therapeutic target in the aging process and/or neurodegenerative diseases. Increased HO-1 activity correlates with protection against stressful conditions, such as hypoxia/ ischemia, oxidative stress, and neuroinflammation [12,15,16]. Furthermore, HO-1 counteracts the transcriptional activity of nuclear factor kappa B (NFkB), which is the master regulator of oxidative stress and the inflammatory response [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies ranging from cell cultures to animal models have demonstrated that resveratrol exhibits antioxidant, anti-inflammatory, anti-aging and antitumor activities [22][23][24][25][26][27][28][29][30]. Resveratrol also protects neurons and astrocytes in several neurological disease models, such as epilepsy, stroke, Alzheimer's and Parkinson's diseases [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%